HUBUNGAN KEKUATAN OTOT LENGAN TERHADAP KETEPATAN SERVIS ATAS BOLA VOLI KLUB LION VCDI DESA PAUH KECAMATAN RAWAS ILIR KABUPATEN MURATARA - Serly Evi Yanti; Azizil Fikri; Muhamaad Suhdy ($$8@@&&$%K, 2022)
This study aims to determine whether there is a relationship between Arm Muscle Strength and Upper Service Accuracy at Lion Vc Club in Pauh Village, RawasIlir District, Muratara Regency. This type of research is quantitative. Quantitative research is a systematic study of the parts and phenomena as well as the results of the data obtained in the form of numbers. The method used in this research is the correlation method. The results of the research conducted showed that the strength of the arm muscles on the accuracy of serving on volleyball is known to have a correlation value between X and Y variables of 0.95 and a df of 15 was obtained in the table the value of "r" product moment at the 5% significant stage was 0.51. And the interpretation table states that r = 0.80 to 1.00 indicates that between the variables x and y there is a very high correlation.